Accelerated vegetation succession but no hydrological change in a boreal fen during 20 years of recent climate change. Issue 12 (2nd May 2021) - Kolari, Tiina H. M.; Korpelainen, Pasi; Kumpula, Timo; Tahvanainen, Teemu
Abstract: Northern mires (fens and bogs) have significant climate feedbacks and contribute to biodiversity, providing habitats to specialized biota. Many studies have found drying and degradation of bogs in response to climate change, while northern fens have received less attention. Rich fens are particularly important to biodiversity, but subject to global climate change, fen ecosystems may change via direct response of vegetation or indirectly by hydrological changes. With repeated sampling over the past 20 years, we aim to reveal trends in hydrology and vegetation in a pristine boreal fen with gradient from rich to poor fen and bog vegetation. We resampled 203 semi‐permanent plots and compared water‐table depth (WTD), pH, concentrations of mineral elements, and dissolved organic carbon (DOC), plant species occurrences, community structure, and vegetation types between 1998 and 2018. In the study area, the annual mean temperature rose by 1.0°C and precipitation by 46 mm, in 20‐year periods prior to sampling occasions. We found that wet fen vegetation decreased, while bog and poor fen vegetation increased significantly. This reflected a trend of increasing abundance of common, generalist hummock species at the expense of fen specialist species. Changes were the most pronounced in high pH plots, where Sphagnum mosses had significantly increased in plot frequency, cover, and species richness. Changes of water chemistry were mainly insignificant in concentration levels and spatial patterns. Although indications toward drier conditions were found in vegetation, WTD had not consistently increased, instead, our results revealed complex dynamics of WTD as depending on vegetation changes. Overall, we found significant trend in vegetation, conforming to common succession pattern from rich to poor fen and bog vegetation. Our results suggest that responses intrinsic to vegetation, such as increased productivity or altered species interactions, may be more significant than indirect effects via local hydrology to the ecosystem response to climate warming. Abstract : We studied global change effects on vegetation and hydrology in a pristine boreal mire in a decadal time‐span. We repeated over 200 measurements of plant species cover, water‐table depth, and several water chemistry variables, after a marked shift to warmer conditions. We did not find significant changes in water chemistry, while remarkable vegetation changes were observed, suggesting that responses intrinsic to vegetation were more significant than indirect effects via local hydrology to the ecosystem response to recent warming. ​